An Italian translation of "Viejas historias de Castilla la Vieja" by Miguel Delibes - de Pieri, Mª Teresa (Estudios de Traducción, 2012)
Miguel Delibes’ works achieved a moderate success in Italy, thus the translations into italian have always been occasional: the first translation, Siesta con Vento Sud dates back to 1959, while the italian edition of Diario de un cazador was published in 1998. This study tries to revise the critical interest about Miguel Delibes, in Italy, through the analysis of some of the short stories appeared in Viejas Historias de Castilla la Vieja. The present article investigates some relevant aspects of the translation process, and takes into consideration the features of Miguel Delibes’ style. The peculiarity of the narrative “I” –often fading out into the cultivated narrator’s voice–, the translation of some sentences of colloquial language, and the difficulty of identifying the author’s ironic point of view, are analysed in the present paper. This study also examines the vocabulary of Miguel Delibes, and its symbolic nuances.
Keywords: Viejas historias de Castilla la Vieja; translation process; colloquial sentences; irony; translation into italian.